МОРФОЛОГИЧЕСКАЯ КАРТИНА ПЕЧЕНИ ПРИ МОДЕЛИРОВАНИИ ЖИРОВОЙ ДИСТРОФИИ РАЗЛИЧНОГО ПРОИСХОЖДЕНИЯ В ЭКСПЕРИМЕНТЕ - Брус, Татьяна Викторовна; Пюрвеев, Сарнг Саналович; Полищук, Полина Анатольевна; Белякова, Елизавета Дмитриевна; Семёнов, Алексей Александрович; Бадаев, Алдар Батрович; Ефремова, Дарья Алексеевна (FORCIPE, 2022)